Psychosocial correlates of adherence self-efficacy and HIV viral suppression among adolescents and young adults in Western Kenya - Deepa Oja; Wenwen Jiang; Barbra A. Richardson; Jacinta Badia; James Kibugi; Kristin Beima-Sofie; Sarah Hicks; Jillian Pintye; Molly R. Altman; Kawango Agot; Grace John-Stewart; Pamela Kohler (PLoS ONE, 2026)
Objective To measure adherence self-efficacy (ASE) to antiretroviral therapies (ART) and evaluate the relationship between ASE, depression, perceived social support, and HIV viral suppression among adolescents and young adults living with HIV (ALHIV) in Kenya. Design Cross-sectional analysis of baseline data from a longitudinal cohort of Kenyan ALHIV. Methods ALHIV were recruited from nine health facilities in western Kenya. Participants completed behavioral surveys at enrollment, and study team members extracted viral load data from a national database. ASE was assessed using a modified HIV-Adherence Self-efficacy Assessment Survey (HIV-ASES), and depression was assessed as a score of ≥ 10 using the PHQ-9. Linear mixed effects regression modeling and general linear mixed effects regression modeling, clustering by facility, were used to determine associations between ASE scores, viral suppression, and correlates of interest. Results Overall, 987 ALHIV age 15 and older were included in this study, 70% were female, 58% ages 15−19, and 57% were attending or had completed at least secondary school. Ninety-six percent had ASE data, 73% (517/703) were virally suppressed, 90% (888/987) scored 9 or below on the PHQ-9, 47% (460/987) reported high perceived social support, and 65% (645/987) were classified as having orphan status. ALHIV who had moderate-to-severe depression had a mean ASE score that was 13.41 points lower (95% CI: −20.12 – −6.52, p < 0.001) than those with none-or-mild depression. Female ALHIV had higher odds of viral suppression (adjusted OR: 1.55, 95%CI: 1.07–2.25, p = 0.02) as did ALHIV with higher social support (adjusted OR: 1.67, 95%CI: 1.17–2.40, p = 0.005). There was no significant association identified between ASE and viral suppression. Conclusions Emotional well-being and social support are essential to improve adherence self-efficacy and viral suppression among youth living with HIV.